a Efektivitas Limbah Bonggol Nanas (Ananas comosus) Sebagai Bahan Antibakteri : Indonesia - Rica Denis; Yurike Yurike; Ari Femi Agustiya (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
The pineapple core has not been utilized optimally, despite containing several active components, one of which is the bromelain enzyme. Bromelain exhibits antibacterial properties. The objective of this study was to determine whether pineapple core extract (Ananas comosus (L.) Merr) is effective in inhibiting the growth of Escherichia coli bacteria. The study employed the disk diffusion test method to measure the clear zone around the blank disk vertically and horizontally using a Vernier caliper with units in millimeters (mm). The treatment was conducted three times with different concentrations, an incubation time of 1 x 24 hours, and a temperature of 37°C. The concentrations tested were 20%, 40%, 60%, and 100%, with ciprofloxacin as the positive control (+). The results of this study showed that a concentration of 20% produced an average inhibition zone of 7.8 mm, 40% produced an average inhibition zone of 18 mm, 60% produced an average inhibition zone of 21 mm, 80% produced an average inhibition zone of 22 mm, and 100% produced an average inhibition zone of 24 mm.